Capacity Building for Teaching English in Universities of Afghanistan (American Journal of Arts and Human Science, 2023)
In the 20th and 21st centuries, English became an essential part of the educational curriculum in schools and universities of Afghanistan, particularly after a period of Taliban dominion that had no stable educational system. The educational system took a new turn in schools, institutes and universities to enter a period of progress. Teaching of English language became popular and many institutes started English language programs to teach students. The English language was included in the curriculums of schools and universities as a mandatory subject due to its acceptance as a global language. The study aims to explore and find out the challenges of teaching English as a foreign language in universities of Afghanistan and to provide techniques for capacity building of teachers for English language teaching. A self-administered questionnaire was used to collect the data from Faculty teaching English in Afghanistan to understand their perspectives on the challenges. Likert scale is used in the research questionnaire to measure the scores allotted by faculty on each challenge. Results will be drawn for data analysis using one sample t-test.